Redescription of Astyanax guaporensis Eigenmann, 1911 (Characiformes: Characidae), a small characid from the rio Madeira basin - Marinho, Manoela M. F.; Ohara, Willian M. (Zootaxa, 2013)
During recent expeditions to several localities in the rio Madeira basin, a poorly known species of Characidae described more than a century ago, Astyanax guaporensis Eigenmann, was collected. The species is herein redescribed based on the type material and many recently collected specimens. The species seems to occur only in the rio Madeira basin, rio Am-azonas drainage. The species is mainly recognized among its congeners by having five to nine maxillary teeth, a series of V-shaped marks on the midlateral line of body, and the absence of a black mark on the caudal peduncle.